Problem-based learning as a facilitator of conceptual change. (August 2015) - Loyens, Sofie M.M.; Jones, Suzanne H.; Mikkers, Jeroen; van Gog, Tamara
Abstract: We investigated whether problem-based learning (PBL) can foster conceptual change. Students were randomly assigned to a PBL, lecture-based, or self-study group, all receiving instruction about the topic of Newtonian laws. Conceptual change was measured from pre- to immediate post-test (directly after instruction) and from immediate post-test to delayed post-test after one week. Results showed that the PBL-group outperformed both the lecture and the self-study group on the immediate post-test. This result supported the hypothesis that PBL can increase the likelihood of conceptual change. The PBL group also outperformed both other groups at the delayed post-test after one week; the decline in conceptual change from immediate to delayed post-test was similar for all three groups. Findings are discussed in terms of cognitive engagement. Highlights: We investigated whether problem-based learning (PBL) fostered conceptual change (CC). CC was greater after learning from PBL than from lectures or self-study only. After one week, this benefit was retained. The decline in scores from immediate to delayed post-test was similar for all groups.